Assessing the inter‐rater and intra‐rater reliability of the Physical Therapy Competence Assessment for Airway Suctioning (PT‐CAAS). (17th February 2022) - Miller, Erin; Brooks, Dina; O'Brien, Kelly K.; Beavers, Lindsay; Stratford, Paul; Nonoyama, Mika; Mori, Brenda
Abstract: Background and Purpose: The Physical Therapy Competence Assessment for Airway Suctioning (PT‐CAAS) is a recently developed measure to assess the clinical competence of physiotherapists who perform airway suctioning with adults. The purpose of this study was to assess the inter‐rater and intra‐rater reliability of the PT‐CAAS. Methods: Scoring rules were developed through expert consultation. Reliability was then assessed using nine videos of suctioning performed in a simulated learning environment. A repeated measures design was used, with two replicate sets of measurements made by each participant for all videos. Data were analyzed using a repeated measures model for the concurrent assessment of inter‐rater and intra‐rater reliability. Participants were physiotherapists with suctioning experience. Results: Twenty physiotherapists completed initial scoring and re‐scoring for all nine videos; their data were included in the analysis. Intraclass correlation coefficients (ICCs) for inter‐rater reliability ranged from 0.569 [lower one‐sided 95% confidence interval (CI): 0.395; standard error of measurement (SEM): 0.963] for infection control to 0.759 (lower one‐sided 95% CI: 0.612; SEM: 0.722) for post‐suctioning assessment and care. The inter‐rater ICC for overall performance was 0.752 (lower one‐sided 95% CI: 0.602; SEM: 0.660). ICCs for intra‐rater reliability ranged from 0.759 (lower one‐sided 95% CI: 0.197; SEM 0.721) for infection control to 0.860 (lower one‐sided 95% CI: 0.544; SEM: 0.550) for post‐suctioning assessment and care. The intra‐rater ICC for overall performance was 0.867 (lower one‐sided 95% CI: 0.559; SEM: 0.483). Discussion: Evidence of moderate to good inter‐rater and good intra‐rater reliability was found; however, the results should be interpreted with caution given the wide CIs and relatively large SEMs. Improved assessor training and assessments of reliability using a larger sample size are recommended.